Biomarkers of pediatric Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis through single-cell transcriptomics - Jie Shen; Yunyan He; Hong Zheng; Jianwen Xiao; Fu Li; Keke Chen; Biyun Guo; Yulei He; Lin Liu; Zhi Lin; Dan Wang; Leping Liu; et al. (Nature Communications)
Abstract Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis (EBV-HLH) is a fatal hyperinflammatory disorder distinct from self-limiting EBV-induced infectious mononucleosis (IM). However, the immunological mechanisms underlying the divergence between benign EBV infection and fulminant HLH—particularly in the absence of inherited immunodeficiency—remains unclear, and systematic comparisons of immune landscapes across EBV-associated disease spectra are lacking. In this study, by enrolling children with IM and healthy volunteers as controls, we utilize single-cell RNA sequencing to identify unique immunological characteristics of EBV-HLH. Our analysis indicates that patients with EBV-HLH exhibite widespread activation of NF-κB signaling pathway. Furthermore, excessive cytokine secretion by T and NK cells is observed, along with a shift in monocyte differentiation towards an inflammatory phenotype, and the aggregation of IDO1+ monocytes. Metabolic pathway analysis reveals that L-kynurenine, a downstream metabolite of IDO1, is specifically elevated in EBV-HLH and mediates the production of multiple pro-inflammatory cytokines. Collectively, our study maps the immune landscape in pediatric EBV-HLH at single-cell resolution, uncovering potential role of IDO1+ monocytes and L-kynurenine as biomarkers.